The Historical Genesis of "Sociology of the Body" as important trend of modern social and humanitarian studies - Yaroslav Рotapenko (Cхід, 2013)
The historical specifical features of somatical analysis in modern sociological studies are considered. The special attention given to the "turn to the body" in sociology as the consequence of wide interdisciplinary dialogue with other social and humanitarian disciplines